The South Seas Onstage - Gamer, Michael (Romanticism on the Net)

(untitled) (Université de Montréal, 2021)
This essay explores how the theater supplied a visual and sonic language for understanding the far-flung reaches of the world and spectatorship more generally. While beginning with Charles Darwin aboard the HMS Beagle, its primary focus is the aftermath of Captain Cook’s first and second voyages in the 1770s and 1780s, especially the roles played by the Royal Academy of Science, the Royal Academy of Art, and London’s Theatre Royals in creating the visual and sonic vocabularies by which British subjects came to imagine the islands and peoples of the South Pacific. Theater’s intense topicality requires taking full stock of the cultural bodies and institutions with which it interacts, and nowhere are such collaborations more visible than in early spectacles that introduced the islands of the South Pacific to the British public. Surveying Harlequin Robinson Crusoe (1781) and Omai; or, A Voyage around the World (1785), the essay explores the roles played by Joseph Banks, Richard Brinsley Sheridan, Philippe Jacques de Loutherbourg, Thomas Linley, and others in shaping how London—and eventually provincial—audiences understood the meaning and import of Cook’s voyages of exploration and colonization.